Formation of Integrated Sheep Village as Effort to Bring Livestock Technology to Farms Community - ., Isbandi (Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Establishing of âIntegrated Sheep Villageâ is one of the dissemination models as well as the media to introduce the technology to farmer. The model can be used as an effort to bring the technologies that have been produced by IRIAP to users (stakeholders). Indonesia Research Institute for Animal Production (IRIAP) has introduced a livestock production model known as "Integrated Sheep Village" in the region of Pandeglang, Banten Province. Through âIntegrated Sheep Villageâ model, farmers are expected to adopt the technology that suits to local condition. Synergy of cooperation and coordination with Research Agency in the area that is AIAT, and local District Animal Husbandry Office, as well as other related institutions became the main model in its development. The model has been successfully done through technology assistance activities as livestock development efforts. Through site-specific technology package that is easy to apply, this model is expected to provide services and to disseminate of research findings optimally to the public. Besides, the model is expected to become Village Breeding Centre to develope certain livestock. Â  Key words: Sheep village, sheep, assistance, technology